Pengembangan Sumber Daya Manusia Melalui Pemanfaatan Teknologi dan Literasi Digital Bagi Pemerintah Desa Ngargogondo (Kreativasi : Journal of Community Empowerment, 2024)
The community partnership program implemented in Wagean Hamlet, Ngargogondo Village, Borobudur District, Magelang Regency, has the aim of assisting the development of human resources for the hamlet government as an effort to develop the community in a sustainable manner. We have previously carried out preliminary observations which found that the people of Wagean Hamlet have great potential for development but do not yet have basic skills in operating technology and digital literacy. With the main background of the community being MSME players and they need knowledge regarding the use of technology and how to provide informative information for the development of their business. The public does not yet have basic knowledge regarding the application of technology and digital literacy skills so.People only follow the flow of technological and information developments without understanding the information they obtain. The results of mapping the obstacles experienced by the Wagean Hamlet government, it is hoped that they can master the basics of technology and digital literacy, to develop the hamlet government system so that it is more organized and informative to the community. The Wagean Hamlet government is expected to be able to master digital literacy so that it can better control the information spread among the community. The results of this service are: partners who receive assistance admit that they understand better how to use technology and have a better understanding of digital literacy.